The Addition of Red Betel Leaf Extract (Piper crocatum) in the Feed of Vannamei Shrimps (Litopenaeus vannamei) for Vibriosis Prevention - Fariq Azhar; Muhammad Junaidi; Bagus Dwi Hari Setyono; Andre Rachmat (Journal of Aquaculture and Fish Health, 2021)
Vibriosis is a type of shrimp disease caused by Vibrio sp. In the disease control of consumption biota, it is highly recommended to use natural ingredients that are not carcinogenic, one of which is red betel leaves (Piper crocatum). This study aims to determine the best dose of red betel leaf extract (P. crocatum) mixed in Vannamei shrimp feed to prevent vibriosis. In this study, shrimps were reared for 40 days at a density of 20 fish/container. The treatments included positive control, P1 (without extract + bacterial infection), negative control P2 (without extract and without bacterial infection), P3 (0.5% extract + bacterial infection), P4 (1% extract + infection), and P5 (2% extract + bacterial infection). The application of red betel leaf extract at a dose of 0.5% resulted in 75% survival after infection with V. parahaemolyticus, Vannamei shrimps of THC 7.70×106 cells/mL, and DHC (hyaline 82.94% granular 20.10%). The number of bacteria and the number of vibrio in the intestine were 52×108 CFU/mL and 12×108 CFU/mL accordingly. The best dose was obtained at P3 (Feed +0.5% red betel leaf extract), seen from the increase in survival rate, the number of hemocytes, differential haemocyte counts, and a decrease in total bacteria, so the application of red betel leaf extract can be used in the cultivation of Vannamei shrimps as an immunostimulant.